Józefa Morelowskiego literackie reakcje na trzeci rozbiór Polski (w kontekście Barda polskiego Adama Jerzego Czartoryskiego). Rekonesans - Górowska, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The problem of the influence of the 1795 political defeat and the crisis of the Polish literary and normative language on the activity of writers immediately after the Third Partition is the main subject of this text. The unjust conviction that after the fall of the Republic there was a total silence amongst poets prevailed for decades. The attention was focused on literary reactions to the loss of the sovereignty of two poets of the last generation of authors of the Polish Enlightenment: Adam Jerzy Czartoryski, who was making his debut (the Polish bard poem) and Józef Morelowski, a young Jesuit clerical student (Laments for the Partition of Poland). Their literary commitment constitutes the token of sincere emotions of patriotism and deep reactions to the loss of independence in spite of a long-term conviction about the disappearance of patriotic poetry. Moreover, opinions of selected critics and literary researchers on the state of literature and the correctness of the view about the silence of poets after 1795 were analysed.